2021
DOI: 10.1002/aoc.6368
|View full text |Cite
|
Sign up to set email alerts
|

Palladium supported on MRGO@CoAl‐LDH catalyzed reductive carbonylation of nitroarenes and carbonylative Suzuki coupling reactions using formic acid as liquid CO and H2 source

Abstract: In the present study, a heterogeneous palladium catalyst system, Pd nanoparticles supported on MRGO@CoAl-LDH, was synthesized and employed in reductive carbonylation of nitroarenes and carbonylative Suzuki coupling reactions using formic acid as CO and H 2 source. The as-obtained heterogeneous catalyst was characterized by Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray analysis (EDAX), thermal gravimetric analysis (TGA), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
(62 reference statements)
0
2
0
Order By: Relevance
“… Amine Carboxylic acid Product Time (min) Yield a (%) M.p. °C (Lit) 30 87 53 (48–51) 90 30 81 116 (114–116) 94 30 67 171 (169.2–170.8) 95 30 81 186 (182–187) 93 30 74 69 (65.2–67) 95 30 83 105 (103–105) 84 …”
Section: Resultsmentioning
confidence: 99%
“… Amine Carboxylic acid Product Time (min) Yield a (%) M.p. °C (Lit) 30 87 53 (48–51) 90 30 81 116 (114–116) 94 30 67 171 (169.2–170.8) 95 30 81 186 (182–187) 93 30 74 69 (65.2–67) 95 30 83 105 (103–105) 84 …”
Section: Resultsmentioning
confidence: 99%
“…11,12 Thus far, several studies have been reported on the one-pot synthesis of N -formamides from nitroarenes using HCOOH or its derivatives. 5,13–16…”
Section: Introductionmentioning
confidence: 99%